2015
DOI: 10.5194/acp-15-1489-2015
|View full text |Cite
|
Sign up to set email alerts
|

Trends of non-methane hydrocarbons (NMHC) emissions in Beijing during 2002–2013

Abstract: Abstract. Non-methane hydrocarbons (NMHCs) play a critical role in the photochemical production of ozone (O3) and organic aerosols. Obtaining an accurate understanding on temporal trends of NMHC emissions is essential for predicting air quality changes and evaluating the effectiveness of current control measures. In this study, we evaluated temporal trends of anthropogenic NMHC emissions during August in Beijing based on ambient measurements during selected summer periods at an urban site in Beijing from 2002 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 55 publications
(101 reference statements)
8
50
1
Order By: Relevance
“…Unfortunately, no systematic VOC observations are available from the SDZ site so that we cannot prove this supposition conclusive. However, a large increase in the anthropogenic emissions of non-methane hydrocarbon (NMHC) can be inferred from the Multiresolution Emission Inventory for China (MEIC) (http://www.meicmodel.org) for Beijing in the period of 2004-2012, which supports our view, although the emission data are questioned by a recent study (Wang et al, 2015).…”
Section: Cause Analysissupporting
confidence: 57%
“…Unfortunately, no systematic VOC observations are available from the SDZ site so that we cannot prove this supposition conclusive. However, a large increase in the anthropogenic emissions of non-methane hydrocarbon (NMHC) can be inferred from the Multiresolution Emission Inventory for China (MEIC) (http://www.meicmodel.org) for Beijing in the period of 2004-2012, which supports our view, although the emission data are questioned by a recent study (Wang et al, 2015).…”
Section: Cause Analysissupporting
confidence: 57%
“…The surrounding area of this site is mainly commercial and residential, and the major nearby emission source of sampling site was vehicular traffic. This site is considered to be representative of a typical urban environment in Beijing (Song et al, 2007;Zhang et al, 2014;Li et al, 2015b;Wang et al, 2015). To evaluate the effect of the control measures, the whole study was divided into two parts: non-control period (11-19 August 2015) and control period (20 August-3 September 2015).…”
Section: Sampling Site Descriptionmentioning
confidence: 99%
“…Therefore, the higher emission of aromatic VOCs will likely result in more SOA formation potential. Existing fuel-effect experimental and model studies have shown that high-aromatic fuel in gasoline fuel will lead to more emissions of primary PM as well as some aromatic VOCs (Zervas et al, 1999;EPA, 2013;Karavalakis et al, 2015;Wang et al, 2016), indicating the considerable potential impact of gasoline aromatic content on SOA production. Furthermore, though aromatic content in diesel fuel may have an insignificant impact on SOA formation (Gordon et al, 2014b), SOA production from gasoline vehicle is considered more sensitive to aromatic content than that from diesel vehicle (Jathar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%